2018
DOI: 10.1002/jcb.26918
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β from M2 macrophages promotes migration and invasion of ESCC cells enhancing epithelial‐mesenchymal transition and activating NF‐κB signaling pathway

Abstract: Despite the phenotype has been established that M2 macrophages promotes the metastasis of ESCC, question still remains as to how the M2 macrophages facilitated metastasis of ESCC cells. To begin with, immunohistochemistry was performed to detect the expression of CD163, one typical surface marker of M2 macrophages in 90 paired ESCC and its normal controls after meta-analyzing the relevant studies regarding M2 macrophages in ESCC, confirming that infiltration of M2 macrophages was significantly linked with lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…It has been previously suggested that EMT could be associated with a pro-tumorigenic microenvironment in lung cancer 41 . In esophageal squamous cell carcinoma, M2 macrophages promote migration, invasion, and enhance EMT 42 . On the other hand, mast cells have been associated with angiogenesis in breast cancer 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that EMT could be associated with a pro-tumorigenic microenvironment in lung cancer 41 . In esophageal squamous cell carcinoma, M2 macrophages promote migration, invasion, and enhance EMT 42 . On the other hand, mast cells have been associated with angiogenesis in breast cancer 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that IL-1β was expressed in human ESCC cell [ 47 ]. IL-1β was also expressed in M2 TAMs in human ESCC [ 13 , 48 ]. We suggest that IL-1β derived from ESCC cells and/or TAMs may induce CCL3 secretion from TAMs; however the role of IL-1β against TAMs in ESCC was not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages are regarded as tumor-promotive and are correlated with poor prognosis in various cancers, including ESCC (43,44). M2 macrophages could promote tumor metastasis by inducing epithelial-mesenchymal transition (EMT) or secreting cytokines such as IL-1β (45). The infiltrated immune cell can induce the host immune response to inhibit or promote the progression of tumor cells in the tumor microenvironment (42).…”
Section: Discussionmentioning
confidence: 99%